The Potential of Synergy – Developing a Tool to Design Ecosystems for Sustainable Soil Management - Boissele, Tsilla (European Journal of Sustainable Development, 2017)
Environmental and economical limitations prompt the search for areas of improvement to reduce the environmental footprint of agriculture, while increasing its resilience and maintaining productivity. We propose a biomimicry approach, where cultivation and productivity are more dependent on intrinsic dynamics than on human/chemical inputs driven by fossil fuels. To specifically target synergetic dynamics and overcome difficulties linked to poor knowledge and hazardous trial-and-error processes, we are developing an informatics tool to design adapted, efficient plant partnerships or clusters. The tool consists of a prediction model that suggests potential win-win plant or other symbiotic relationships, flexible enough to exploit information about local soil/climatic conditions. As the tool gains strength from generated data, it evolves into a simulation model for several-component ecosystem-like systems. In this way, the tool establishes a solid base to support and accelerate applicability of intercropping–type methods, providing realistic expectations about growth and harvest over time, including ecological criteria such as biodiversity. Thus, the tool provides a way out of the deforestation/agriculture dilemma, and opens up possible human soil use during remediation of polluted areas, with significant consequences in many different domains affected by human soil use, including environment, soil stability, health, and climate.